Análise comparativa entre métodos de diagnóstico da leucoplasia pilosa oral em crianças infectadas pelo vírus Imunodeficiência adquirida humana tipo 1: estudo citopatológico, imunocitoquímico e molecular - Maciel, Vanessa de Abreu (2008)
The oral hairy lekoplakia (OHL) described for the first time in 1984 is an opportunist infection caused by the Epstein-Barr virus (EBV), typically found in patients immunologicly compromised mainly the carrying patients of the virus of the immunodeficiency human (HIV). Clinically it is presented as a white lesion, not detachable, with inexact edges, most frequently located on the lateral border of the tongue. By being similar to other white entities that occur in the mouth, its diagnosis does not have to be given only through the clinical comment. The ideal is the accomplishment of diagnosis methods that make possible the identification of the EBV or the representative nuclear alterations of the cytopathic effects of the viral infection in the epithelial cells. Such effects are seen in the cytopathology, which constitutes an excellent diagnosis method of this lesion, being able, also, to detect its subclinical phase. Literature tells that the presence of OHL in HIV+ adults is related with fall of the immune function, being for this considered an excellent marker prognostic of this illness. However, its comment in HIV infected pediatric patients is rare. The objective of this work was to compare the methods of diagnosis (cytopathology, Immunocytochemistry and Molecular - ISH) of the OHL in children HIV+. All the composed sample for 100 pediatric patients HIV+ was submitted to the collection of material, independent of the lesion presence, through two scraped in each lateral border of tongue, with endocervical brush. The scraped material of the first one was submitted to the technique of cytopathology. The material collected in the second scraping was destined for accomplishment of the techniques of ICQ and in situ hybridization (ISH). The frequency of OHL found in the studied sample was greater that the told one in literature in pediatrics patients infected by the HIV. Of the 200 slides where the cytopathology was carried through, in 25 (12.5%) slides, that correspond the 14 patients, the diagnosis of OHL was gotten, based on the findings of the representative nuclear alterations of the cytopathic effects of the EBV. And of the 110 slides where the ICQ was carried through, in 15 (13.64%) slides, 13 patients, got the diagnosis of OHL, based on the immunopositivity reation of the express antibody anti-BZLF-1 for the EBV in the replicative phase. Of these, nine patients had gotten the diagnosis in the two techniques, while nine cases had been opponents (five patients alone had only had diagnosis for cytopathology and four for the ICQ). Thus, having moderate disgnostic agreement between the techniques, without a statistical significant difference; one concluded that although the cytopathology to present similar performance in the diagnosis of the OHL in relation to the ICQ, presents minor time of processing and inferior cost. These facts make to indicate the cytopathology as technique of routine for the diagnosis and accompaniment of the OHL, a time that the studies that use only the clinical findings in the diagnosis of the OHL, does not reflect its true frequency, therefore the diagnosis of subclinical hairy lekoplakia is not made.